2015
DOI: 10.4172/2150-3508.1000129
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight Relationship, Body Morphometrics, and Condition Based on Sexual Stage in the Rusty Crayfish, Orconectes rusticus Girard, 1852 (Decapoda, Cambaridae) with Emphasis on Management Implication

Abstract: The objectives for this study were to evaluate patterns in growth and condition between the carapace length (CL)-wet weight (W wt) relationship between male form I, male form II, female, and juvenile life stages. This study compared the carapace length (CL) to the postorbital length (POCL), carapace width (CW), carapace depth (CD), and abdomen width (ABW) measurements taken from males form I, males form II, and females. This study also compares the CL, ChL, and ABW of rusty crayfish within the native and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The relationships between crayfish morphology and waterbody type were analyzed using principal component analysis (PCA) and generalized linear models (GLMs). Previous studies have reported that crayfish morphology is sexually dimorphic (Anderson and Simon 2015;Mazlum et al 2007). Therefore, we compared the morphology of male and female in the tributary and lake populations separately.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between crayfish morphology and waterbody type were analyzed using principal component analysis (PCA) and generalized linear models (GLMs). Previous studies have reported that crayfish morphology is sexually dimorphic (Anderson and Simon 2015;Mazlum et al 2007). Therefore, we compared the morphology of male and female in the tributary and lake populations separately.…”
Section: Discussionmentioning
confidence: 99%
“…Estimating length–weight relationships (LWRs) is useful when comparing life histories and morphological aspects of a fish population during different periods and regions and is a necessity for fish stock assessments and management (Anderson & Simon, ; Lavergne, Zajonz, & Sellin, ; Li, Jin, Shan, & Dai, ; Philips, ). This study describes the LWRs of four economically important teleost fishes caught in the South China Sea.…”
Section: Introductionmentioning
confidence: 99%